Length – length relationships of 16 Caribbean elasmobranchs. (14th June 2017) - Tagliafico, A.; Rangel, M. S.; Rago, N.
Summary: Elasmobranchs are commonly landed without fins and heads; however, the knowledge of total length is necessary for fishery management. We provide useful equations to extrapolate partial from elasmobranch carcasses lengths, to total lengths. Length‐Length Relationships (LLR) are described for 16 commercial elasmobranch species all included in the IUCN Red List: Hexanchus nakamurai, Heptranchias perlo, Squalus cubensis, Squatina dumeril, Scyliorhinus boa, Mustelus minicanis, M. higmani, M. norrisi, Carcharhinus acronotus, C. falciformis, C. limbatus, Galeocerdo cuvier, Rhizoprionodon lalandii, R. porosus, Sphyrna lewini and Pseudobatos percellens . This study provide new LLR equations and rsepresent an improvement in the knowledge of these species.